To compare the efficacy of hyperbaric levobupivacaine (0.5%) versus hyperbaric bupivacaine (0.5%) in the subarachnoid block for infraumbilical surgeries - Rachna Gupta; Jitendra Agrawal; Preeti Goyal; Shreya Putta; Bharat Tarachandani (Asian Journal of Medical Sciences, 2024)
Background: Spinal anesthesia is the neuraxial regional anesthesia technique used in infraumbilical surgeries such as inguinal hernia, hydrocele, hysterectomy, and lower limb surgeries. Levobupivacaine and bupivacaine are local anesthetic agents used for spinal anesthesia. Aims and Objectives: The aim of the study was to compare the efficacy of hyperbaric levobupivacaine (0.5%) versus hyperbaric bupivacaine (0.5%) in subarachnoid blocks for infraumbilical surgeries. Materials and Methods: A total of 112 patients with American Society of Anesthesiologists grades 1 and 2 scheduled for infraumbilical surgeries were randomly divided into two groups. Group L received 3 mL of hyperbaric levobupivacaine, and group B received 3 mL of hyperbaric bupivacaine intrathecally. The onset of sensory block, onset, and duration of motor block, duration of analgesia and time of first rescue analgesia, hemodynamic parameters, and post-operative side effects, if any, were recorded. Results: The time of onset of sensory block at T10 for group L was 03.16±00.29 min and for group B was 02.16±00.27 min and the time of onset of motor block was higher in group L (03.29±00.32 min) compared to group B (02.45±00.32 min). Duration of motor block was significantly shorter in group L (209.80±6.44 min) compared to group B (252.41±11.49 min). All these findings were statistically significant. Conclusion: Levobupivacaine had a delayed onset of sensory and motor block as compared to bupivacaine, but due to its short duration of motor block and better hemodynamic profile, it seems to be a better alternative to bupivacaine.